Scalable territorial identity – Designing the communication of complexity - Luca Casarotto; Monica Oddone (Agathón)
The design linked to the identity of places is an activity of particular interest for the design discipline, especially in its narration and value communication process addressed to a broad public. The design actions take place in a context of great complexity regarding the stratification of meanings and pre-existing visual systems, confronting very different territorial scales (from the nation to the single typical product). The experimentation described in the contribution presents a potential methodology for defining a scalable and multimodal territorial identity. This methodology, applied to a reference territorial context, is designed with tools specifically developed to counter the widespread fragmentation of communication, which usually determines situations of poor recognisability and strategic effectiveness.